Influence of brightness artifacts in ocular tomography scans - Arizcuren, Ana R.; España, España (Jornada de Jóvenes Investigadores del I3A, 2024)
Corneal transparency is crucial for ocular health. This study, based on image processing and statistical analysis, uses clinical corneal images to investigate the influence of spurious brightness on transparency. It was found that an increase in brightness significantly reduces apparent transparency (r=0.57, p